2023
DOI: 10.1002/adfm.202305109
|View full text |Cite
|
Sign up to set email alerts
|

Activating the Inert Na1 Sites in Na2FePO4F Toward High Performance Sodium Storage

Abstract: Na2FePO4F, an iron‐based fluorophosphate with facile 2D sodium ion channels, is considered as a promising cathode material for sodium‐ion batteries because of low cost, resource abundance, and nontoxicity. However, its application is considerably restricted by the limited intrinsic electronic conductivity and specific capacity. Herein, a doping strategy represented by Cu2+ is proposed to boost the electrochemical performance, attributed to the derivation of a new active Na3 site originated from the inert Na1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This can change the electronic structure and surface activity of the original inert sites, thus regulating the reaction activity of the site. The crystal structure of Na 2 FePO 4 F contains two kinds of Na sites in the Na layer, denoted as active Na2 and inert Na1 (Figure a) . When doping Cu atoms, a portion of the original Na1 sites transforms into the newly formed Na3 site, resulting in an average bond length of Na–O/F from 2.50 to 2.52 Å (Figure b).…”
Section: Atomic Manufacturing For Electrochemical Performancementioning
confidence: 99%
See 2 more Smart Citations
“…This can change the electronic structure and surface activity of the original inert sites, thus regulating the reaction activity of the site. The crystal structure of Na 2 FePO 4 F contains two kinds of Na sites in the Na layer, denoted as active Na2 and inert Na1 (Figure a) . When doping Cu atoms, a portion of the original Na1 sites transforms into the newly formed Na3 site, resulting in an average bond length of Na–O/F from 2.50 to 2.52 Å (Figure b).…”
Section: Atomic Manufacturing For Electrochemical Performancementioning
confidence: 99%
“…(b) Depiction of the Na 3 environment deriving from Na1 in FeCu-0.05. (c) Cycling performance at 10 C. Reproduced with permission from ref . Copyright 2023 Wiley-VCH.…”
Section: Atomic Manufacturing For Electrochemical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…However, the poor intrinsic conductivity and limited active sodium sites of β-Na 2 FePO 4 F make its rate capability and reversible capacity unsatisfactory. Huang et al proposed a doping strategy represented by Cu 2+ to improve the electrochemical performance, and the prepared Na 2 Fe 0.95 Cu 0.05 PO 4 F/C composites showed better electrochemical performance than the previously reported Na 2 FePO 4 F . Jin et al found that the average voltage could be increased, and the band gap and the Na ion diffusion barrier could be reduced by co-doping four metal elements (Ti, Co, Ni, and Sn) .…”
Section: Introductionmentioning
confidence: 99%
“…23 However, the poor intrinsic conductivity and limited active sodium sites of β-Na 2 FePO 4 F make its rate capability and reversible capacity unsatisfactory. chemical performance than the previously reported Na 2 FePO 4 F. 24 Jin et al found that the average voltage could be increased, and the band gap and the Na ion diffusion barrier could be reduced by co-doping four metal elements (Ti, Co, Ni, and Sn). 25 Kacemi et al found that Mn doping could significantly increase the conductivity and voltage of β-Na 2 FePO 4 F, resulting in a high-energy density SIB cathode.…”
Section: Introductionmentioning
confidence: 99%